Maternal, but not paternal or grandparental, caffeine intake is associated with childhood obesity and adiposity: The Lifeways Cross-Generation Cohort Study. Issue 6 (28th May 2019) - Chen, Ling-Wei; Murrin, Celine M; Mehegan, John; Kelleher, Cecily C; Phillips, Catherine M; ,
ABSTRACT: Background: Maternal caffeine intake is associated with adverse birth outcomes, but its long-term influence on offspring adiposity outcomes is not well studied. Furthermore, few studies have investigated paternal and grandparental caffeine intake in relation to offspring outcomes. Objective: To study the associations between maternal, paternal, and grandparental caffeine intake and offspring childhood adiposity. Design: The core study sample consists of 558 mother-child pairs from the Lifeways Study. Caffeine intake was derived from relevant food items in a self-administered validated food frequency questionnaire in early pregnancy. Children's body mass index (BMI) and waist circumference (WC) were measured at 5- and 9-y follow-up. Childhood overall and central obesity were defined as age- and sex-specific BMI z-score > International Obesity Task Force cut-off and WC z-score > 90 th percentile, respectively. Multiple linear and logistic regressions were used to assess associations. Results: Study mothers had a mean age of 30.8 y and a mean prepregnancy BMI (kg/m 2 ) of 23.7. In adjusted models, maternal caffeine intake was associated with a higher offspring BMI z-score [β (95% CI): 0.13 (0.06, 0.21) for year 5 and 0.17 (0.04, 0.29) for year 9; per 100 mg/d increment in maternal caffeine intake], WC z-score [β (95% CI): 0.09 (0.01, 0.17) for year 5 and 0.19 (0.05, 0.32) for year 9], and a higher risk of offspring overall obesity [OR (95% CI): 1.32 (1.11, 1.57) for year 5 and 1.44 (1.10, 1.88) for year 9] and central obesity [1.28 (1.02, 1.60) for year 5 and 1.62 (1.12, 2.34) for year 9]. The influence was stronger for coffee caffeine than tea caffeine. No consistent associations were observed for paternal and grandparental caffeine intake. Conclusions: Maternal antenatal, but not paternal or grandparental, caffeine intake is associated with higher offspring adiposity and obesity risk at age 5 and 9 y, with stronger associations observed for coffee caffeine. This prospective observational study was registered at the ISRCTN Registry as ISRCTN16537904.